The Question Of Entrepreneurship In Algeria Between The Will Of The State And Realities On The Ground - Nezai Fatima, Zohra; Hachemi, Tayeb (Université de M'sila, 2020)
: Abstrac Many economists have outlined the fact that the questions of growth, development, evolution are totally linked with the place of enterprises (notably the smallest ones) in the economy, meaning that entrepreneurship is dealing with the creation of this kind of enterprise, but also to resolve the fundamental problem of unemployment and to supply the government in many areas. For this, this subject has been completely abandoned and ignored by deciders in the Algerian case, and now with the changes in the world economy, the collapse of petrol prices and the role of entrepreneurs in the economy, the government is trying to reconsider its place in the national, but the main question remain if this decision is conform with the real environment and realities of domestic economy. That’s our concern in this paper that we try to examine deeply concerning the case of Algeria.
Keywords: Key-words:Entrepreneurship-Algeria-Markets-Management-Employment-Local environment